IDENTIFICATION OF GEOLOGICAL STRUCTURES USING INH METHOD AND MODELLING OF GEOTHERMAL SYSTEM USING GRAVITY DATA IN GEOTHERMAL AREA OF PANTAR ISLAND, EAST NUSATENGGARA - Farish Rizkiansyah, Moch.
The territory of Indonesia has a large potential for geothermal energy resources. One of them is the Pantar Island geothermal area, Alor Regency, East Nusa Tenggara Province. Therefore, exploratory research is needed to determine geothermal areas that have the potential and can be utilized. Gravity measurement data used in this study were obtained from the Center for Coal and Geothermal Mineral Resources (PSDMBP) in 2015. The data was processed into a complete Bouguer anomaly map, then separated regional anomalies and residual anomalies using the Moving Average and Polynomial Trend Surface Analysis methods. The anomaly response on the Bouguer anomaly map, regional anomaly map, and residual anomaly map shows a lineation pattern trending Southwest-Northeast. Analysis of rock unit contact boundaries to identify the presence of geological structures in the study area was carried out using First Horizontal Derivative (FHD) and Improve Normalized Horizontal (INH) techniques. The INH map shows the existence of a fault with a lineation pattern trending Southwest-Northeast and Northwest-Southeast. Furthermore, based on the results of the 2.5D forward modeling of the residual anomaly, as well as data from derivative analysis supported by geological, geochemical and other geophysical data, a geothermal conceptual model in the study area can be made. Based on this model, it can be estimated that the source of heat comes from the volcanic activity of Mount Sirung, reservoir rock which is thought to be at a depth of more than 1000 meters, and caprock which is thought to be alteration rock scattered around geothermal manifestations. Reservoir water is thought to originate from meteoric water. In addition, it can be identified that the recharge area is in a low topographic area, the discharge area is around Beang Hill as an upflow zone, while the outflow zone is on the northern slope towards Tubbe hot water and Beang hot water which appears in the eastern part of Top Sirung.